Traumatic extraction of upper central incisors - Janković Svjetlana; Žuža Aleksandra; Davidović Bojana; Simić Ivana; Davidović Lado (Serbian Medical Society - Dental Section, Belgrade, 2018)
Introduction Tooth and other oral tissue damage can occur at any time of life. Traumatic extraction is a complex traumatic injury characterized by complete dislodgement of the tooth from its alveolus. The diagnosis of traumatically injured teeth includes X-rays and a detailed clinical examination. Case report A twelve-year-old boy reported at the dental clinic of the Faculty of Medicine due to the injury in the anterior maxillary region. It was a sport injury. The time elapsed since the accident was 2 hours and 20 minutes. According to the clinical examination and X-rays the diagnosis was: The teeth 11 and 21 - Complete traumatic dental avulsion and fracture; 22- Hypodontia and chin contusion and laceration. The teeth were brought in physiological solution. After applying local anesthetic, soft tissue was cleaned, the teeth positioned back in their alveoli and an immobilizing splint of fiberglass fibers placed. The patient was administered antibiotics and recommended tetanus prophylaxis. Seven days after the injury, teeth were treated endodontically. After one month, the immobilizing splint was removed. The tooth 21 was definitely obturated and composite buildups were done on both teeth. Calcium hydroxide dressing was left in the canal of the tooth 11. One month and 3 weeks after the injury, a fistula appeared above the tooth 11, and the treatment was finally completed after seven months. Conclusion Traumatic tooth injuries, of any kind, require urgent treatment as time loss usually reduces chances for successful treatment. One year after the injury, the patient had no symptoms and the result was functional and aesthetically acceptable.